2007
DOI: 10.1177/0142723707081652
|View full text |Cite
|
Sign up to set email alerts
|

Early word-object associations and later language development

Abstract: Early language skills vary considerably across children, especially before the age of about two years. Thus, it can be difficult to distinguish between `late bloomers' and children who show a language delay or impairment. Here we present the results of a longitudinal study wherein toddlers' performance on a looking-time-based `Switch' task of word-object association (Stager & Werker, 1997) was related to the children's later language skills. Word-object association performance at 17 or 20 months was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
(43 reference statements)
6
32
0
1
Order By: Relevance
“…To summarize, our findings add to the growing body of research that shows that measures of processing linguistic information obtained early in life correlates with later language development (Bernhardt, Kemp, & Werker, ; Fernald, Perfors, & Marchman, ; Höhle, van de Vijver, & Weissenborn, ). An early assessment of prosodic skills—which is one of the earliest perceptual abilities that can be tested in infants—may indicate children at risk for developing a language‐related impairment.…”
Section: Discussionsupporting
confidence: 64%
“…To summarize, our findings add to the growing body of research that shows that measures of processing linguistic information obtained early in life correlates with later language development (Bernhardt, Kemp, & Werker, ; Fernald, Perfors, & Marchman, ; Höhle, van de Vijver, & Weissenborn, ). An early assessment of prosodic skills—which is one of the earliest perceptual abilities that can be tested in infants—may indicate children at risk for developing a language‐related impairment.…”
Section: Discussionsupporting
confidence: 64%
“…For instance, a longitudinal design with typically-developing children could help determine if implicit learning abilities predict subsequent speech and language abilities assessed several years later (see Bernhardt, Kemp, & Werker, 2007; Gathercole & Baddeley, 1989; Newman, Bernstein Ratner, Jusczyk, Jusczyk, & Dow, 2006; Tsao, Liu, & Kuhl, 2004). Such a finding would provide support for the hypothesis that implicit learning plays a causal role in language development.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, performance in the minimal pair Switch task at 17 -18 months is correlated with both concurrent (Kemp et al submitted) and later (Bernhardt et al 2007) measures of vocabulary size and language development more generally. We now turn to studies of minimal pair word-learning in bilinguals to examine what this research has revealed about the microstructure of bilingual acquisition.…”
Section: Same Trialmentioning
confidence: 98%